2019
DOI: 10.5152/tjg.2019.19141
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of JAM-A (rs790056) and LFA-1 (rs8058823) gene variants in Turkish colorectal cancer patients

Abstract: Background/Aims: Lymphocyte function-associated antigen 1 (LFA-1) is a transmembrane glycoprotein expressed on the surface of leukocytes and containing the binding domain for junctional adhesion molecule-A (JAM-A). The aim of the present study was to evaluate the effects of JAM-A and LFA-1 variants on the formation of colorectal cancer and metastasis.Materials and Methods: A total of 82 subjects with colorectal cancer and 67 healthy subjects were studied. DNA was isolated from blood samples, and variations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Therefore, we aimed to determine the distributions of JAM-A rs790056 and LFA-1 rs2230433 variations in patients with leiomyoma, as well as their individual and combined effects. So far, studies investigating JAM-A and LFA-1 have been related to melanoma, coronary artery diseases (22), atherosclerosis (23), breast cancer ( 16), cerebral ischemiareperfusion injury (24), kidney cancer (25)and colorectal cancers (26). To our knowledge, JAM-A and LFA-1 gene variations in leiomyoma have been investigated for the first time in our study.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, we aimed to determine the distributions of JAM-A rs790056 and LFA-1 rs2230433 variations in patients with leiomyoma, as well as their individual and combined effects. So far, studies investigating JAM-A and LFA-1 have been related to melanoma, coronary artery diseases (22), atherosclerosis (23), breast cancer ( 16), cerebral ischemiareperfusion injury (24), kidney cancer (25)and colorectal cancers (26). To our knowledge, JAM-A and LFA-1 gene variations in leiomyoma have been investigated for the first time in our study.…”
Section: Discussionmentioning
confidence: 80%
“…Colorectal cancer is one of the deadliest carcinoma types worldwide. Recent research of the involvement of F11R/JAM-A and LFA-1 genetic variants in colorectal cancer development and metastasis was the first investigation of these gene variations in patients [ 110 ]. The authors revealed that the F11R/JAM-A rs790056 variation could influence the development of colorectal carcinoma (CC genotype has a threefold increased risk of colorectal cancer occurrence) and suggested that this variation could be evaluated as a potential predictive biomarker of this cancer type.…”
Section: F11r/jam-a Expression In Cancermentioning
confidence: 99%
“…The authors revealed that the F11R/JAM-A rs790056 variation could influence the development of colorectal carcinoma (CC genotype has a threefold increased risk of colorectal cancer occurrence) and suggested that this variation could be evaluated as a potential predictive biomarker of this cancer type. Unfortunately, they did not define the relationship between genotypes and F11R/JAM-A expression (protein expression and soluble F11R/JAM-A levels or mRNA were not measured) [ 110 ].…”
Section: F11r/jam-a Expression In Cancermentioning
confidence: 99%
“…Moreover, it regulates many cellular processes, including angiogenesis (Naik et al, 2008), cell migration (Azari et al, 2010;Wang and Liu, 2022) and adhesion (Mandell et al, 2005), leukocyte transendothelial migration (Corada et al, 2005;Khandoga et al, 2005), intercellular permeability (Laukoetter et al, 2007), epithelial-tomesenchymal transition (EMT) (Communal et al, 2020) and platelet activation (Babinska et al, 2002). In the literature, JAM-A is described as a protein involved in the pathogenesis of neurological disorders (Padden et al, 2007), cardiovascular diseases (Babinska et al, 2019;Koenen and Weber, 2022;Rath et al, 2022;Wang and Chen, 2022), rheumatoid arthritis (Fang et al, 2016), inflammatory bowel disease (Vetrano and Danese, 2009), and many types of neoplastic diseases including breast (McSherry et al, 2009;Murakami et al, 2011;Vellanki et al, 2019;Bednarek et al, 2020;Vences-Catalan et al, 2021;Smith et al, 2022), lung (Magara et al, 2017;Zhao et al, 2017), nasopharyngeal (Jiang et al, 2019;Dai et al, 2021), head and neck (Kurose et al, 2016;Kakiuchi et al, 2021), testicular (Tarulli et al, 2013), thyroid (Orlandella et al, 2019), colorectal (Caykara et al, 2019;Lampis et al, 2021), gastric (Huang et al, 2014), endometrial (Koshiba et al, 2009), cervical (Akimo...…”
Section: Introductionmentioning
confidence: 99%